Taxing Pensions of an Internationally Mobile Labor Force: Portability Issues and Taxation Options - Robert Holzmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
There is a rising share of individuals spending at least some part of their working life abroad and acquiring pension rights. While the portability of pensions and other social benefits has received some analytical attention over the recent decade there is currently limited analytical guidance on the taxation of retirement provisions within a country, and there is virtually none for the taxation of internationally portable pensions. For both national and international taxation of pensions, the actual taxation approaches are characterized by a high level of diversity, complexity and inconsistency within and across countries that risk harming labor mobility and creating fiscal unfairness. The proposed taxation approach for internationally portable pensions mixes notional front-loaded taxation (as the tax due on contributions/savings is deferred) with actual back-loaded taxation as the taxes are due when the benefits are disbursed (in source or residency country) or when accumulated savings effectively leave the country. This approach promises to establish broadly neutrality for international labor mobility decisions, fiscal fairness of tax revenue around retirement provisions between source and residency country, and bureaucratic efficiency, including a consistency with EU regulations and most double-taxation treaties.
Keywords: H20; H24; H55; 330; income taxation; cross-border labor mobility; portable pensions; double taxation treaties; EET; TEE; individual and fiscal fairness; bureaucratic effectiveness